Triplex DNA logic gate based upon switching on/off their structure by Ag+/cysteine. Issue 21 (11th September 2015) - Xiao, Zhiyou; Zhu, Houya; Xin, Aiping; Li, Yubin; Ling, Liansheng
Abstract : Based upon switching on/off the structure of triplex DNA by Ag + /cysteine, a triplex DNA logic gate was constructed using TAMRA/BHQ-2-modified oligonucleotides. Abstract : The formation of intramolecular triplex DNA can be regulated by Ag + and Cys (cysteine), which switch off/on the fluorescence of the oligonucleotides, 5′-TAMRA-TTC TCT TCC TCT TCC TTC TGA CGA CAG TTG ACT CTT CCT TCT CCT TCT CTT-BHQ-2-3′ (Oligo 1) and 3′-GAA GGA AGA GGA AGA GAA-5′ (Oligo 2). Based on this principle, sensors for Ag + and Cys are developed. The sensor for Ag + has a linear range of 2.5 nM–40 nM and a detection limit of 1.8 nM, whereas the sensor for Cys has a linear range of 10.0 nM–120.0 nM and a detection limit of 8.2 nM. Furthermore, the fluorescence is reversible with the alternate addition of Ag + and Cys. We constructed a DNA logic gate using Ag + and Cys as the input, and the fluorescence intensity as the output. The DNA logic gate is simple; moreover, it has a fast response and good reversibility.